Efeitos de estresses bióticos sobre os parâmetros ecofisiológicos e componentes de produção de quatro variedades de cana-de-açúcar - Silva, Fábio Leal Santos da (2015)
Brazil is the main world producer of sugarcane (Saccharum ssp.), being the activity of the Brazilian sugarcane industry in continuous expansion, which can be seen due to increasing both the production capacity as agricultural areas intended for the cultivation. However, the increase of the production costs and the expansion of cultivation to less productive areas have increasingly demanded strategies to safeguard the sector's profitability. In this sense, studies of environmental factors that limit the yield of sugarcane crops are fundamental and can cite the biotic stresses caused by pathogenic microorganisms and the weeds. Plants respond differently to various types of stress, and, in general, are firstly affected in their physiological and photosynthetic properties. Therefore, the analysis of ecophysiological parameters - being this a tool to detect small deviations from normality of the photosynthetic performance - can provide useful information about the behavior of plants under stressful conditions caused by the disease and weed competition. Thus, this study aimed to evaluate the behavior of four different sugarcane varieties submitted to the stresses caused by the bacterium Leifsonia xyli subsp. xyli (Lxx) - causal agent of Ratoon stunting disease (RSD) - and competition with the weed plant Brachiaria decumbens Stapf., correlating the production data with the ecophysiological responses resulting from the stress condition. To this finality, stem segments with just one bud were planted in plastic trays and kept in a greenhouse, being the seedlings subsequently transplanted to the field, where were measured both yield parameters (biometric and technological), the fluorescence of chlorophyll a and the gas exchange of plants subject, or not, to mentioned stressors. The experimental design used was the randomized block design with four replications, in a split-plot scheme, being the plots composed by varieties Co 997, RB867515, RB92579 and RB951541; and the subplots by the induction or not of stress factor. Regarding Lxx inoculation, RB92579 and RB951541 varieties were less sensitive to the RSD effects, since both ecophysiological and yield parameters were just a little bit affected by disease, while RB867515 and Co 997 varieties underwent changes in many parameters, highlighting the decline of photosynthetic rate and the reduction of height and diameter of the stalks. Regarding weed competition with B. decumbens, the four varieties tested were affected in all parameters, resulting in significant losses of yield, being that the RB92579 variety showed higher competitive ability than the others. Thus, the use of ecophysiological analysis tool is feasible to aid the work of selection of tolerant sugarcane genotypes to typical adverse situations of his cultivation.